2023
DOI: 10.12688/f1000research.130649.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of chronic kidney disease among Indonesian adult population: Results from the 2018 Indonesia Basic Health Research

Abstract: Background: Three out of ten cases of chronic kidney disease (CKD) are cause by type 2 diabetes mellitus (T2DM). In addition, nutritional status, consumption of unhealthy foods, high blood pressure, and smoking habits were also previously identified as risk factors to CKD but there is a scarcity of data from Indonesia. Therefore, we sought to determine the risk factors using a predictive model for the incidence of CKD in Indonesia based on the Indonesia Basic Health Research 2018. Methods: Secondary data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Chronic Kidney Disease (CKD) or renal failure is a condition characterized by a decline in kidney function due to damage, which can be evidenced by albuminuria, hematuria, structural and pathological abnormalities in the kidneys, or a glomerular filtration rate (GFR) of less than 60 mL/min/1.73 m² for at least three months (Kidney Health Australia, 2020). The prevalence of CKD in Indonesia increased from 0.2% in 2013 to 0.3% in 2018 (Hidayangsih et al, 2023;Rachmah et al, 2023). Additionally, a study found that the prevalence of CKD in Indonesia in 2018 was 0.38%, with varying rates across different provinces, such as 0.64% in North Kalimantan and 0.18% in West Sulawesi (Ro'di et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic Kidney Disease (CKD) or renal failure is a condition characterized by a decline in kidney function due to damage, which can be evidenced by albuminuria, hematuria, structural and pathological abnormalities in the kidneys, or a glomerular filtration rate (GFR) of less than 60 mL/min/1.73 m² for at least three months (Kidney Health Australia, 2020). The prevalence of CKD in Indonesia increased from 0.2% in 2013 to 0.3% in 2018 (Hidayangsih et al, 2023;Rachmah et al, 2023). Additionally, a study found that the prevalence of CKD in Indonesia in 2018 was 0.38%, with varying rates across different provinces, such as 0.64% in North Kalimantan and 0.18% in West Sulawesi (Ro'di et al, 2023).…”
Section: Introductionmentioning
confidence: 99%